Geomorphological Hazards, Land Use Planning and Emergency Management - Oliveira, Sérgio (2020)
In the last decades, Portugal was affected by several geomorphological hazards that produced high levels of destruction and disruption on human activities, particularly due to the inappropriate occupation of areas where natural hazardous phenomena occur. To cope against the consequences of these hazards, a set of legal instruments has been implemented in the last 30–40 years by national initiative or by transposition to the national law of European Directives within the thematic of risk assessment and management. This chapter broadly presents the planning and emergency management legal framework in Portugal, as well as the specific normative instruments for the major geomorphological hazards that influence land use regulation.